2020
DOI: 10.3389/fphys.2020.00591
|View full text |Cite
|
Sign up to set email alerts
|

Increased Serum Klotho With Age-Related Aortic Stiffness and Peripheral Vascular Resistance in Young and Middle-Aged Swine

Abstract: The anti-aging function of Klotho gene has been implicated in age-related diseases. The physiological importance of Klotho in the progression of arterial stiffness with aging, however, remains unclear. The goal of this study is to determine the correlation of circulating Klotho with early age-related aortic stiffening and peripheral hemodynamics. We measured serum Klotho levels in a group of pigs with age ranges of 1.5-9 years and investigated the relationship between Klotho levels and biomarkers of aortic sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Therefore, evaluation of circulating klotho concentrations or klotho genotypes could help identify patients at higher risk of developing age-related cardiovascular morbidities. However, previous studies on the relationship between circulating klotho and blood pressure and arterial stiffness had small sample sizes 13 , used a case–control design 14 , performed analyses only in select patients 13 , 15 , 16 , measured peripheral blood pressure only 8 , or reported conflicting results 15 , 17 . In a recent study in young and middle-aged swine, elevated klotho secretion was associated with increased aortic stiffness and peripheral vascular resistance with aging 17 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, evaluation of circulating klotho concentrations or klotho genotypes could help identify patients at higher risk of developing age-related cardiovascular morbidities. However, previous studies on the relationship between circulating klotho and blood pressure and arterial stiffness had small sample sizes 13 , used a case–control design 14 , performed analyses only in select patients 13 , 15 , 16 , measured peripheral blood pressure only 8 , or reported conflicting results 15 , 17 . In a recent study in young and middle-aged swine, elevated klotho secretion was associated with increased aortic stiffness and peripheral vascular resistance with aging 17 .…”
Section: Introductionmentioning
confidence: 99%
“…However, previous studies on the relationship between circulating klotho and blood pressure and arterial stiffness had small sample sizes 13 , used a case–control design 14 , performed analyses only in select patients 13 , 15 , 16 , measured peripheral blood pressure only 8 , or reported conflicting results 15 , 17 . In a recent study in young and middle-aged swine, elevated klotho secretion was associated with increased aortic stiffness and peripheral vascular resistance with aging 17 . In the present population-based study, we investigated the associations between the serum klotho (i.e., secreted α-klotho) concentrations and the peripheral/central blood pressure and arterial stiffness based on the carotid–femoral pulse wave velocity (cfPWV).…”
Section: Introductionmentioning
confidence: 99%
“…It remains unclear how such vascular changes could affect limb perfusion. Aortic stiffening has been associated with increased peripheral vascular resistance, and such changes can lead to decreased limb perfusion (Guo & Kassab, 2020). Moreover, human studies have demonstrated a decreased vasodilatory response in patients with significant coronary calcification (Wang et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, arterial stiffness was increased in animals with calcified arteries and was associated with medial elastin degradation, suggesting that MAC may lead to worse outcomes in part due to its effects on arterial compliance. Other studies have also demonstrated that decreased arterial compliance is associated with increased peripheral vascular resistance and a decreased vasodilatory response, which may contribute to decreased perfusion ( 53 , 54 ). However, it is likely that other factors also contribute to the complex mechanisms behind MAC and decreased perfusion, warranting further investigation.…”
Section: Introductionmentioning
confidence: 99%